Effect of MnO2 addition on dielectric, piezoelectric and ferroelectric properties of 0.2Pb(Zn1/3Nb2/3)O 3-0.8Pb(Zr1/2Ti1/2)O3 ceramics - Athipong Ngamjarurojana (2018)
Piezoelectric materials are presently being extensively developed for applications such as ultrasonic motors and piezoelectric transformers. In this study, the dielectric, piezoelectric, and ferroelectric properties of MnO 2-doped 0.2Pb(Zn1/3Nb2/3) O3-0. 8Pb(Zr1/2Ti1/2)O3 (hereafter 0.2PZN-0.8PZT), which is the morphotropic phase boundary composition of the PZN-PZT system, were investigated. It was found that crystal structure moved to rhombohedral side when increasing MnO2 content. With the addition of MnO2, Curie temperature Tc, the piezoelectric constant d33, and electromechanical coupling factor kp were slightly decreased, but the mechanical quality factor Qm was significantly increased. The P-E and s-E loop demonstrated decreased Pr and strain level but increased E c with addition of MnO2. These results clearly showed the significance of MnO2 addition on the electrical properties of the PZN-PZT system with "hard" characteristics.